2019
DOI: 10.1002/mdp2.90
|View full text |Cite
|
Sign up to set email alerts
|

Core‐shell nanofibers for developing self‐healing materials: Recent progress and future directions

Abstract: The knowledge of self‐healing was developed to ensure more durable and reliable engineering materials. Healing agent encapsulation has shown to be one of the most promising approaches in self‐healing technology. The healing agents were encapsulated within micro/nanocapsules, micro/nanofibers, and vascular‐based networks. Among the methods, using core‐shell nanofibers showed a compromising potential for the development of self‐healing nanofibers with the minimum drawbacks and limitations. The aim of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…An effective self-healing nanofiber with a thin layer can recover the mechanical properties after being damaged by tensile, delamination, and bending forces . The core/shell (C/S) fiber morphologies enable large amounts of SH agents to entrap large amounts in their core . It has been shown that the addition of healant-loaded C/S nanofibers substantially enhanced the primary mechanical performance and resulted in the self-healing of composites that could recover their initial mechanical performance after failing …”
Section: Self-healing Core-shell Nanofibermentioning
confidence: 99%
See 2 more Smart Citations
“…An effective self-healing nanofiber with a thin layer can recover the mechanical properties after being damaged by tensile, delamination, and bending forces . The core/shell (C/S) fiber morphologies enable large amounts of SH agents to entrap large amounts in their core . It has been shown that the addition of healant-loaded C/S nanofibers substantially enhanced the primary mechanical performance and resulted in the self-healing of composites that could recover their initial mechanical performance after failing …”
Section: Self-healing Core-shell Nanofibermentioning
confidence: 99%
“…It still needs to be extended to systems such as aerogels, hydrogels, and biomedical materials. Also, there is a scope of advancement in constructing nanocapsules and healants-loaded nanofibers by altering the operational framework to obtain better efficacy …”
Section: Self-healing Core-shell Nanofibermentioning
confidence: 99%
See 1 more Smart Citation
“…Nanofiber could significantly reinforce the properties of the composite. [37,38] As a one-dimensional nanofiber, aramid nanofiber (ANF) presents ultra-high strength, high modulus, large specific surface area and excellent stability due to the strong interactions between molecular chains such as hydrogen bonds, van der Waals forces and high crystallinity [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…The embedment of well‐dispersed nanofillers into a polymer matrix has been demonstrated to be a very appealing idea to improve the comprehensive performance of polymer nanocomposites, which is closely related to the increased interfacial area and reinforced interaction between the polymer matrix and the nanofillers . Nanofiller dispersion can be improved by optimizing the polymer‐nanofiller interface . The good interfacial adhesion between the polymer matrix and the nanofiller can be accomplished through using porous fillers .…”
Section: Introductionmentioning
confidence: 99%